Near-infrared germanium PIN-photodiodes with >1A/W responsivity - Hanchen Liu; Toni P. Pasanen; Tsun Hang Fung; Joonas Isometsä; Antti Haarahiltunen; Steven Hesse; Lutz Werner; Ville Vähänissi; Hele Savin (Light: Science & Applications)
Abstract Even though efficient near-infrared (NIR) detection is critical for numerous applications, state-of-the-art NIR detectors either suffer from limited capability of detecting incoming photons, i.e., have poor spectral responsivity, or are made of expensive group III-V non-CMOS compatible materials. Here we present a nanoengineered PIN-photodiode made of CMOS-compatible germanium (Ge) that achieves a verified external quantum efficiency (EQE) above 90% over a wide wavelength range (1.2–1.6 µm) at zero bias voltage at room temperature. For instance, at 1.55 µm, this corresponds to a responsivity of 1.15 A/W. In addition to the excellent spectral responsivity at NIR, the performance at visible and ultraviolet wavelengths remains high (EQE exceeds even 100% below 300 nm) resulting in an exceptionally wide spectral response range. The high performance is achieved by minimizing optical losses using surface nanostructures and electrical losses using both conformal atomic-layer-deposited aluminum oxide surface passivation and dielectric induced electric field -based carrier collection instead of conventional pn-junction. The dark current density of 76 µA/cm2 measured at a reverse bias of 5 V is lower than previously reported for Ge photodiodes. The presented results should have an immediate impact on the design and manufacturing of Ge photodiodes and NIR detection in general.